2018
DOI: 10.1111/jcpp.12918
|View full text |Cite
|
Sign up to set email alerts
|

Early warm‐rewarding parenting moderates the genetic contributions to callous–unemotional traits in childhood

Abstract: High warm/rewarding parenting may partly impede the genetic expression of CU traits. Developmental models of CU traits need to account for such gene-environment processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 50 publications
6
29
1
Order By: Relevance
“…Research has demonstrated that maternal warmth may interrupt the development of affective psychopathic traits in youth (Kimonis et al, 2013; Waller et al, 2014). Thus, while behavioral genetic studies suggest that approximately half of the variance in psychopathy is explained by genetics (see Thomson, 2019 for review), maternal warmth may offset the development of psychopathic traits (Henry et al, 2018). However, if the mother becomes imprisoned then genetically vulnerable youth may lack the environmental protective factors to inhibit the development of affective psychopathic traits.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that maternal warmth may interrupt the development of affective psychopathic traits in youth (Kimonis et al, 2013; Waller et al, 2014). Thus, while behavioral genetic studies suggest that approximately half of the variance in psychopathy is explained by genetics (see Thomson, 2019 for review), maternal warmth may offset the development of psychopathic traits (Henry et al, 2018). However, if the mother becomes imprisoned then genetically vulnerable youth may lack the environmental protective factors to inhibit the development of affective psychopathic traits.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, if the human brain is evolutionarily designed to survive and thrive in adverse environments, when individuals are raised in harsh rearing scenarios, as are the majority of detained youth, their brains also become calibrated for such environments (Sheskin et al 2014;Vagos et al 2016Vagos et al , 2017Vagos et al , 2018. However, while the presence of traumatic experiences seems to contribute to threat focused and antisocial behaviors, psychopathic traits seems to be predicted by rearing environments that are marked by both the presence of traumatic experiences as well as by the absence of warmth and safeness experiences (Henry et al 2018;Pasalich et al 2011;Ribeiro da Silva et al 2019c). Young offenders with psychopathic traits tend therefore to be focused on short-term goals, presenting an overdeveloped and hypervigilant threat system and an under responsive soothing system as well as central emotional dysfunctions (Ribeiro da Siva et al 2015).…”
Section: (…)"mentioning
confidence: 99%
“…The variation in heritability estimates for young children could be due to the different measures and reporters used, and these issues may be compounded by longitudinal non-invariance. That is, there is a distinct possibility that researchers using very young samples may be tapping into a psychological construct that differs from the traditional conceptualization of CU traits seen in adolescents and adults (e.g., Obradović et al, 2007) The picture of CU trait heritability among general population samples of individuals in late childhood, adolescence, and early adulthood (aged 7-19) is much less variable, ranging from 36-67% (Bezdjian, Raine, Baker, & Lynam, 2011;Blonigan, Hicks, Kreuger, Patrick, & Iacono, 2006;Ficks, Dong, & Waldman, 2014;Henry et al, 2018a;Henry et al, 2018b;Henry, Pingault, Boivin, Rijsdijk, & Viding, 2016;Kendler, Patrick, Larsson, Gardner, & Lichtenstein, 2013;Larsson, Andershed, & Lichtenstien, 2006;O'Nions et al, 2015;Taylor, Loney, Bobadilla, Iacono, & McGue, 2003;Mann, Briley, Tucker-Drob, & Harden, 2015;Tuvblad, Bezdjian, Raine, & Baker, 2014;Viding et al, 2013;Viding, Frick, & Plomin, 2007). Furthermore, two studies of this age range suggest that genetic factors account for a substantial proportion of stable variation in CU traits across time; 58% from age 17 to 24 (Blonigan et al, 2006) and up to 89% across ages 7-12 (Henry et al, 2018a).…”
Section: Quantitative Genetic Studiesmentioning
confidence: 99%